2022
DOI: 10.2183/pjab.98.008
|View full text |Cite
|
Sign up to set email alerts
|

RET receptor signaling: Function in development, metabolic disease, and cancer

Abstract: The RET proto-oncogene encodes a receptor tyrosine kinase whose alterations are responsible for various human cancers and developmental disorders, including thyroid cancer, non-small cell lung cancer, multiple endocrine neoplasia type 2, and Hirschsprung's disease. RET receptors are physiologically activated by glial cell line-derived neurotrophic factor (GDNF) family ligands that bind to the coreceptor GDNF family receptor , (GFR,). Signaling via the GDNF/ GFR,1/RET ternary complex plays crucial roles in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 120 publications
(129 reference statements)
0
28
0
Order By: Relevance
“…Using the (33). In addition, there is sufficient evidence that RET plays an important role in other developmental and metabolic disorders (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the (33). In addition, there is sufficient evidence that RET plays an important role in other developmental and metabolic disorders (42).…”
Section: Discussionmentioning
confidence: 99%
“…Using the strategy of combining gene-gene interaction analysis with case-control study, Wang et al demonstrated for the first time that the genetic markers of RET , ARHGEF3 , and CTNNAL1 and the related genetic interaction network can change the susceptibility risk of HSCR in the Han population ( 33 ). In addition, there is sufficient evidence that RET plays an important role in other developmental and metabolic disorders ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…RET protein has a tyrosine kinase intracellular domain linked to an outer cysteine-rich extracellular domain and four cadherin-like domains through transmembrane ( 16 , 17 ). The RET gene forms a ternary complex with Glial cell line-derived neurotrophic factor (GDNF) family ligands (GFLs) and GDNF family co-receptors (GFR α1-4) leading to autophosphorylation of RET-intracellular domain, which activates downstream signaling pathways like PI3K/AKT, RAS/MAPK, JAK/STAT, and PKA/PKC, whose activation or inhibition has an important impact in cell survival, proliferation, migration, and differentiation ( 18 , 19 ). Figure 1 illustrates the constitutive patterns of the RET proteins.…”
Section: Ret Fusion and Its Detectionmentioning
confidence: 99%
“…RET is a transmembrane receptor tyrosine kinase, which is coded by proto-oncogene RET , and was first discovered in T cell lymphoma [ 3 ]. In normal cells, RET is involved in the process of fetal development of hematopoietic, genitourinary, gastrointestinal, and nervous systems.…”
Section: Introductionmentioning
confidence: 99%
“…While gene fusions are more common in papillary thyroid carcinoma (PTC), in around 10–20% of patients, they are much less common in non-small cell lung cancer (NSCLC), in around 1–2% of patients. On the other hand, point mutations in RET gene are common in sporadic medullary thyroid cancer (MTC), in 60–90% of patients, and in multiple endocrine neoplasia syndrome type 2 (MEN2) [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%